2022
DOI: 10.4047/jap.2022.14.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of fully- and pre-crystalized chair-side CAD-CAM lithium disilicate restorations after required and additional sintering processes

Abstract: PURPOSE The aim of this study was to investigate shade changes in fully- and pre-crystalized CAD-CAM lithium disilicate crowns after the required and additional firing processes. MATERIALS AND METHODS One hundred and five crowns of shade A1 with high translucency were milled out of CAD-CAM lithium disilicate blocks and categorized as follows (n = 15): (1) restorations fabricated from Straumann n!ce with no additional sintering process; (2) restorations fabricated from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The authors of [ 19 ] have concluded that NLD had color stability either similar to or higher than LDS, while the color change in both materials was unacceptable regardless of the resin cement shade. In another study, LDS was found to maintain its shade after required and additional crystallization, whereas NLD differed from its original shade even after the first crystallization firing [ 16 ]. Considering the novelty of NLD and the fact that the present study is the first to address the comparison of NLD and ZLS in terms of color stability, these findings need to be substantiated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors of [ 19 ] have concluded that NLD had color stability either similar to or higher than LDS, while the color change in both materials was unacceptable regardless of the resin cement shade. In another study, LDS was found to maintain its shade after required and additional crystallization, whereas NLD differed from its original shade even after the first crystallization firing [ 16 ]. Considering the novelty of NLD and the fact that the present study is the first to address the comparison of NLD and ZLS in terms of color stability, these findings need to be substantiated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new lithium disilicate called nano-lithium disilicate glass-ceramic (NLD; Amber Mill, Hass, Gangneung, Korea) has been marketed [ 7 , 8 , 12 ]. NLD differs from currently available lithium silicate ceramics, as its translucency is adjustable depending on the crystallization process [ 16 ]. Even though NLD has started to gain attention, the number of studies on this material is scarce [ 7 , 12 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dental treatments with CAD/CAM technology can fulfill patient esthetic demands from single to multiple ceramic restorations [ 10 , 11 ]. Lithium disilicate is a well-known dental ceramic with high esthetics and fracture resistance [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%